Aplikasi Pengajuan Judul Skripsi Berbasis Web Pada Jurusan Teknologi Informasi - Farras Naufal Zaky; Noor Alam Hadiwijaya; M.Farman Andrijasa (JURNAL VOKASI TEKNIK, 2024)
The implementation of the final project in higher education often faces obstacles in managing and monitoring progress, especially in the Department of Information Technology, Samarinda State Polytechnic. Submission of the final project title which is still done manually using physical forms and Google Forms results in a slow process and is limited by place and time. This research aims to design and build a web-based final project title submission application. The method used is analysis and design with waterfall modeling, using the PHP programming language, Laravel framework. The result of this research is a web application system that can improve the efficiency and effectiveness of final project management in the Information Technology Department, so that the process runs more smoothly and transparently. The conclusion of this research is that the web-based final project title submission application is designed for students, helps admins manage final project titles and supervisor submissions efficiently, and manage final project trial schedules with scheduling, coordination, and monitoring features and provides significant benefits for study programs, admins, and students, making it easier to submit titles, optimizing communication, and helping the approval and scheduling process.